Dryinidae (Hymenoptera, Chrysidoidea) da estação ecológica de Jataí, Luiz Antônio, SP, Brasil - Versuti, Danielle Roberta [UNESP] (2014)
This study aimed to identify the species of Dryinidae in three phytophysiognomies of the Estação Ecológica do Jataí in Luiz Antonio county, Sao Paulo State, Brazil and assess their abundance, population dynamics and collection methodologies. Sampling of Hymenoptera was fortnightly, between December 2006 and November 2009, in areas of Brazilian savannah, riparian vegetation and savannah woodland. In each area were installed two Malaise traps and two sets of five Moericke traps; in riparian vegetation were installed two light traps, between November 2007 and November 2009. The count data Dryinidae included the effect of year of collection, sex, and method of collection; the count data of Dryinidae over time were analyzed using a logistic model as measures in time by using PROC GENMOD. The diversity of Dryininae species caught by using Malaise traps was compared through rarefaction curves, obtained by bootstrapping with resampling. Were obtained 1721 exemplars of Dryinidae from five subfamilies: Aphelopinae (873 exemplars; 50.7% of the total), Dryininae (371; 21.6%), Anteoninae (300; 17.4%), Gonatopodinae (159; 92%), and Bocchinae (18; 1.0%). In the overall population, the increase of Dryinidae occurred from September; significant differences were observed between the abundances of Dryinidae collected in 2007 and 2008 and in 2008 and 2009. From Aphelopinae were identified Aphelopus Dalman (858 exemplars / 98.3 % of the total collected) and Crovettia Olmi (15 / 1.7 %); the highest frequencies of Aphelopinae were recorded in the spring and summer of 2008 and 2009 and, significant differences were observed at the three years; the interaction between males and females of Aphelopus differed significantly with deviation for males; Aphelopinae was more abundant in riparian vegetation, with significant differences between their abundances in riparian vegetation and Brazilian savannah and savannah ...